A prospective clinico-pathological study of cervical lymphadenopathy - N. R., Narender; J., Yadagiri Rao (International Surgery Journal, 2017)
Background: Lymphadenopathy refers to one or more lymph nodes that are abnormal in size, consistency or number. There are various causes for lymphadenopathy which range from benign conditions to malignant either primary or secondary from draining primary tumour. Lymphadenopathy can be localised to a single group or generalised. Methods: Prospective observational study was performed for the patients attending outpatient department of general surgery at Kamineni academy of medical sciences, LB nagar Hyderabad, Telangana with complaints of enlarged or swollen lymph nodes in the neck. This study included 46 cases. In cases where fine needle aspiration cytology was inconclusive and there was need for excision biopsy, only these cases were included in the study. After biopsy lymph node was sent for gross and microscopic examination for expert opinion from department of pathology. Results: The present study includes 46 patients in a period of two years from 01-8-2015 to 31-7-2017. Of these case tuberculosis lymphadenopathy (n=25,54.3%) was the most common aetiology followed by nonspecific chronic lymphadenopathy (n=16,34.7%) followed by some relatively rare cases and unusual presentation Schwannoma, pleomorphic adenoma, Kikuchi disease, non-Hodgkin’s lymphoma and secondaries from carcinoma tongue (n=1,2.1%). Conclusions: In the present prospective study tubercular lymphadenopathy was the most common cause for cervical lymphadenopathy followed by chronic nonspecific lymphadenopathy.